The prevalence, incidence, and persistence of self-reported visual impairment among Chinese population with diabetes mellitus: evaluation from a nationally representative survey, 2015–2018 - Zhou, Yifan; Wei, Jin; Wang, Ning; Chen, Yisheng; Fang, Cheng; Zhou, Minwen; Zhou, Xinrong; Luo, Jianfeng; Wang, Xiaodong; Peng, Qing (Frontiers in Public Health, 2023)
Aims Our aim was to investigate the prevalence, incidence, and persistence of visual impairment (VI) and their correlates among the Chinese population with diabetes mellitus (DM) over 3 years. Materials and methods The China Health and Retirement Longitudinal Survey is the first nationally representative longitudinal survey of the Chinese population. A cross-sectional analysis of prevalent VI in 2015 consisted of 2,173 participants with DM. A longitudinal observation of incident and persistent VI consisted of 1,633 participants from 2015 to 2018. Risk factors of VI were identified via univariate and multivariate logistic regression analyses. Results Among our study population with DM, 11.8% reported VI in 2015, 4.5% had persistent VI from 2015 to 2018, and 8.9% developed VI in 2018. Factors identified to be correlated to VI (p < 0.05) were older age, being a woman, lower educational attainment, living in a rural area, application of DM medication and non-pharmacological treatment, receiving DM-related tests, use of spectacles, and poorer health status. Conclusion This most recent national data provides a baseline for future public health initiatives on VI among the Chinese population with DM. With multiple risk factors identified, these could provide concurrent targets for various public health strategies and interventions with the aim of reducing the burden of VI among the population with DM in China.